SSTR2 associated with neuronal apoptosis after intracerebral hemorrhage in adult rats. (4th March 2018) - Tan, Xiang; Wang, Shuyao; Guo, Changyun; Qian, Min; Zhang, Xinli; Wan, Peng; Yu, Chao; Geng, Baojian; Ke, Kaifu; Shen, Jiabing; Song, Yan; Yu, Min
Abstract: Objective: SSTR2 is a member of superfamily of SST receptor (SSTR), and widely expressed in the brain; however, the knowledge of its functions in area adjacent to hematoma after intracerebral hemorrhage (ICH) is still limited. Method: The role of SSTR2 in the processes of ICH was explored by conducting an ICH rat model. Western blot and immunohistochemistry were employed to examine the level of SSTR2 in area adjacent to hematoma after ICH. Immunofluorescent staining was used to observe the spatial correlation of SSTR2 with cellular types adjacent to hematoma after ICH. RNA interference specific to SSTR2 was adopted in PC12 cells to clarify the causal correlation between SSTR2 and neuronal activities. Results: Increased expression of SSTR2 was observed and restricted to the neurons adjacent to hematoma following ICH. Immunofluorescent staining showed that SSTR2 was significant increased in neurons, but not astrocytes or microglia. Increasing SSTR2 level was found to be accompanied by the up-regulation of activated caspase-3 and the down-expression of p-Akt in a time-dependent manner. What's more, using SSTR2 RNA interference (SSTR2-RNAi) in PC12 cells, we indicated that SSTR2 might have a pro-apoptotic role in neurons. Conclusion: We speculated that SSTR2 might exert its pro-apoptotic function in neurons through inhibiting Akt activity following ICH.